2021
DOI: 10.1039/d1ra03472c
|View full text |Cite
|
Sign up to set email alerts
|

Absolute content determination by quantitative NMR (qNMR) spectroscopy: a curious case of aldosterone

Abstract: 1D/2D-NMR based extensive analyses of the real structure of aldosterone, elucidating the plausible diastereomeric hemiacetal/hemiketal tautomers and a qNMR based method of absolute content determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…suggesting the presence of an aldehyde at position 18 which, due to the proximity of the 11hydroxy group, forms an hemiacetal and a bicyclical acetal [21,28,29]. Once X-ray crystallography and NMR became available, it was shown that aldosterone in crystal form is the bicyclical acetal [30] (Fig 1 ), while in solution it is a mixture of the readily interconverted hemiacetal and bicyclical acetal forms [29,31].…”
Section: Isolation and Chemical Characterization Of Adrenal Cortical ...mentioning
confidence: 99%
See 4 more Smart Citations
“…suggesting the presence of an aldehyde at position 18 which, due to the proximity of the 11hydroxy group, forms an hemiacetal and a bicyclical acetal [21,28,29]. Once X-ray crystallography and NMR became available, it was shown that aldosterone in crystal form is the bicyclical acetal [30] (Fig 1 ), while in solution it is a mixture of the readily interconverted hemiacetal and bicyclical acetal forms [29,31].…”
Section: Isolation and Chemical Characterization Of Adrenal Cortical ...mentioning
confidence: 99%
“…Reichstein, who had isolated 50 mg of the steroid, demonstrated that oxidation of the steroid yielded a γ-lactone [21,[26][27][28], suggesting the presence of an aldehyde at position 18, which, due to the proximity of the 11β-hydroxy group, forms a hemiacetal and a bicyclic acetal [21,28,29]. Once X-ray crystallography and NMR became available, it was shown that aldosterone in crystal form is the bicyclic acetal [30] (▶ Fig 1 ), while in solution, it is a mixture of the readily interconverted hemiacetal and bicyclic acetal forms [29,31]. The parent structure of an aldehyde in position 13 drawn in many publications has never been confirmed in solution or solid state due to the very high reactivity of the -CHO group at C-13 with the 11β-hydroxy (forming a hemiacetal) and the 11β-hydroxy, the -CHO group at C-13, and 20-keto which form the more stable bicyclic acetal.…”
Section: Isolation and Chemical Characterization Of Adrenal Cortical ...mentioning
confidence: 99%
See 3 more Smart Citations